Assessment of Change in Dynamic Psychotherapy - Høglend, Per (American Psychiatric Press, Inc, 2000)
Five scales have been developed to assess changes that are consistent with the therapeutic rationales and procedures of dynamic psychotherapy. Seven raters evaluated 50 patients before and 36 patients again after brief dynamic psychotherapy. A factor analysis indicated that the scales represent a dimension that is discriminable from general symptoms. A summary measure, Dynamic Capacity, was rated with acceptable reliability by a single rater. However, average scores of three raters were needed for good reliability of change ratings. The scales seem to be sufficiently fine-grained to capture statistically and clinically significant changes during brief dynamic psychotherapy.